tillage and mulching influence of on soil water balance under pineapple crop (Ananas comosus (l) Merr) - SOSSA, Elvire Line; HOUNSOU, Bidossessi Mathieu; AGBANGBA, Codjo Emile; ADEGNANDJOU, Adémola Jules Ayindé; TCHEGNIMONHAN, Comlan Ulrich; SINTONDJI, Luc Olivier; AMADJI, Guillaume Lucien; AGBOSSOU, Kossi Euloge; Hounhouigan, Djidjoho Joseph (My University, 2020)
Pineapple is Benin's third largest agricultural export product after cotton and cashew nuts. Its productivity is affected by water deficit. An experiment was conducted in southern Benin to assess the influence of tillage and mulching on soil water balance under pineapple cultivation. The plant material consists of the pineapple "SugarLoaf" variety. The experimental design used was a split plot with 4 replications where the main factor was the tillage method and the secondary factor, the usage of pineapple crop residues. Soil moisture was evaluated monthly by the gravimetric method, which allowed the calculation of water stocks and the estimation of the water balance at each phenological stage. The data were analyzed using the Excel software. The results revealed that soil water stocks are higher under ridging than under flat tillage during the vegetative and flowering stages in opposite to the fruiting-harvesting stage. Burying of fresh crop residues results in higher soil water stocks followed by surface mulching of residues during all phenological stages. Plants experienced water stress throughout the crop cycle (ETR/ETM <1), but more during the vegetative stage.
Keywords: water deficit; drainage; gravimetric method; evapotranspiration; soil water stock.